PENGARUH MODEL ACTIVE LEARNING TIPE EVERYONE IS A TEACHER DENGAN STRATEGI KARTU PANGGILAN TERHADAP PRESTASI BELAJAR IPS SISWA KELAS VIII DI SMP NEGERI 7 BANDA ACEH - Kurnia Rezeki; zainal Abidin (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2018)
ABSTRACTThis researh entitled "The Influence of Active Learning Model Type Everyone Is A Teacher With Call Card Strategy To Student Achievement of IPS Class VIII Students in SMP Negeri 7 Banda Aceh" this aims to determine the influence of active learning model of everyone type is a teacher by using the calling card strategy to the achievement of IPS student learning of class VIII in SMP Negeri 7 Banda Aceh. In this study researchers used a quantitative approach and the type of experimental research. The population in this study is all students of class VIII in SMP Negeri 7 Banda Aceh consists of five classes, amounting to 159 students. The sample of this research is class VIII2 as experiment class and class VIII1 as control class which consist of 32 students each. Data collection techniques in this study using tests and documentation. The stage of data analysis techniques in this study are (1) calculate the average value; (2) calculate the variance and standard deviation; (3) normality test of data distribution; (4) homogeneity test of variance; and (5) t-test. Based on the data analysis stage it is obtained: the average value of the experimental class and control class is 80.62:74,34. The variance and standard deviations of the experimental class were 79.98 and 8.94 while the control classes were 51.58 and 7.18. The experimental class experimental test was 3.89 and control class 1.11. Homogeneity test of variance of final test of experiment and control class is 1.55. And the t-test result is 3.14. Based on the data analysis above, it can be concluded that the average value of the experimental class is higher than the control class. The data distribution of the final test score of the students in the experimental class and the control class is normally distributed based on the significant significance level x2count ≤ x2table, that is 2.82 ≤ 7.81 and 1.11 ≤ 7.81, for homogeneity test Fcount ≤ Ftabel = 1.55 ≤ 1 , 82 then the experimental class data variance and the homogeneous control class. The result of t-test in analyzing the effect of learning result by using the calling card strategy obtained t-test that is tcount = 3.14 while ttable = 2,00. Means that tcount ttables= 3.14 2.00. Thus according to the testing criteria, Ha is accepted. Keywords:Influence, Active Learning, Type Everyone is A Teacher, Call Card Strategy, IPS Learning Outcomes.  ABSTRAKPenelitian yang berjudul “Pengaruh Model Active Learning Tipe Everyone Is A Teacher Dengan Strategi Kartu Panggilan Terhadap Prestasi Belajar IPS Siswa Kelas VIII di SMP Negeri 7 Banda Aceh” ini bertujuan untuk mengetahui pengaruh model active learning tipe everyone is a teacher dengan menggunakan strategi kartu panggilan terhadap prestasi belajar IPS siswa kelas VIII di SMP Negeri 7 Banda Aceh. Dalam penelitian ini peneliti menggunakan pendekatan kuantitatif dan jenis penelitian eksperimen. Populasi dalam penelitian ini adalah seluruh siswa kelas VIII di SMP Negeri 7 Banda Aceh terdiri dari lima kelas yang berjumlah 159 siswa. Sampel penelitian ini ialah kelas VIII2 sebagai kelas eksperimen dan kelas VIII1 sebagai kelas kontrol yang masing-masing terdiri dari 32 orang siswa. Teknik pengumpulan data dalam penelitian ini menggunakan tes dan dokumentasi. Adapun tahap teknik analisis data dalam penelitian ini adalah (1) menghitung nilai rata-rata; (2) menghitung varians dan simpangan baku; (3) uji normalitas sebaran data; (4) uji homogenitas varians; dan  (5)  uji-t. Berdasarkan tahap analisis data tersebut maka diperoleh: nilai rata-rata kelas eksperimen adalah 80,62  dan kelas kontrol 74,34. Varians dan simpangan baku kelas eksperimen adalah 79,98 dan 8,94 sedangkan kelas kontrol 51,58 dan 7,18. Uji normalitas kelas eksperimen adalah 3,89 dan kelas kontrol 1,11. Uji homogenitas varians tes akhir kelas eksperimen dan kontrol adalah 1,55. Dan hasil uji-t adalah 3,14. Berdasarkan hasil analisis data diatas, dapat disimpulkan bahwa nilai rata-rata kelas eksperimen lebih tinggi daripada kelas kontrol. Sebaran data nilai tes akhir siswa pada kelas eksperimen dan kelas kontrol berdistribusi normal berdasarkan taraf siginifikan x2hitung ≤ x2tabel, yaitu 2,82≤ 7,81 dan 1,11 ≤ 7,81, untuk uji homogenitas Fhitung≤Ftabel = 1,55 ≤ 1,82 maka varians data kelas eksperimen dan kelas kontrol homogen. Hasil uji-t dalam menganalisis pengaruh hasil belajar dengan menggunakan strategi kartu panggilan diperoleh uji-t yaitu thitung = 3,14 sedangkan ttabel = 2,00. Berarti bahwa thitung ttabel, = 3,14 2,00. Dengan demikian sesuai dengan kriteria pengujian, maka Ha diterima. Kata Kunci: Pengaruh, Active Learning, Tipe Everyone is A Teacher, StrategiKartu Panggilan, Hasil Belajar IPS.